Pengembangan Karakter Anak Usia Dini Dalam Keluarga Dengan Model Learning Observation Berbasis Mendarang Di Seko - Wingki; Ferialdi Agasta (Montessori Jurnal Pendidikan Kristen Anak Usia Dini, 2025)
Family plays an important role in the formation of children's character. Therefore, families must always faithfully accompany children during their growth and development. But the reality today, especially in big cities, parents prioritize their jobs and positions rather than accompanying their children during their growth and development. This article wants to show how great the influence of family togetherness is in the formation of early childhood character. To achieve this goal, the author wants to raise the culture of mendarang in Seko Lemo, which is a culture of warming oneself around the kitchen together with all family members. Apparently, this culture also greatly influences children in forming their character. Through the method of literature and field studies, and using Albert Bandura's learning observation approach as a theoretical lens, it can be concluded that the culture of mendarang forms the character of children who have a friendly attitude towards guests and others, are independent, and foster high self-confidence in children. These characters are very important for children in their future lives